Desenvolvimento de proposta formativa em pensamento computacional na prática docente: o uso do ScratchJr - Sandra Regina Sanches Ribas (2022)
This training proposal for Basic Education teachers offers a course to develop Computational Thinking (PC) that allows the creative and critical use of technology, based on problem solving and Creative Learning (CA). To this end, we seek to develop, apply and analyze a training course in PC, based on the mediation of the ScratchJr tool, identifying the levels of understanding of the concept of PC by teachers from the Municipal Network of Belo Horizonte (RME-BH) and elements of the PC present in their pedagogical practices, before and after participating in the course, analyzing possible paths and instruments to develop the PC, through the pedagogical practices of teachers. Our theoretical tripod used as constructs: digital competences, PC and Creative Learning. This research has a qualitative approach, with an exploratory character and as a qualitative investigation method we used the case study. As methodological instruments, we applied questionnaires and online interviews, and participant observation. This research is justified by its contribution in the training of teachers of the Initial Years of Elementary School in public schools, operating the ScratchJr tool, promoting the development of the PC in a playful and accessible way, favoring the student, in the breadth of their cognitive and authorial capacities, becoming the protagonist of their own learning and, thus, strengthening them in their physical and digital citizenship. In the characterization of the focus group, there is a diversity in the teaching experience of the course participants, proven during the course. Our attention was drawn to the diversity of active methodologies used by course participants, with emphasis on Project-Based Learning (PBL) with 18.2%. ScratchJr was not known by most course participants, but it had good acceptance and productive development. The implementation of narratives in this context, using the storyboard, has the strategy of versatility for any disciplinary and interdisciplinary project, working with elements of AC, STEAM and developing skills that contemplate the PC. In the group of eight course participants, there was harmony and agreement, bringing a rich collaborative contribution to the process, validating the work in pairs and legitimizing the methodology used. Returning to the objectives of this work, we consider that the course can serve as a teaching improvement instrument regarding the introduction of visual programming by blocks using ScratchJr. We were able to identify that the concept of CP can be constructed by course participants in order to create references and meaning within their own practice. The course participants were able to identify moments of teaching that already dialogued with the development of the PC, in this way we believe that, with the consolidated concept and mastery of tools, plugged and unplugged, that facilitates the acquisition of this competence. In this context, we can conclude that we answered the research problem that dealt with the association of unplugged pedagogical practices associated with ScratchJr, in the development of the PC. We are developing a group of articulators thinking about hybrid, plugged and unplugged practices, which involve the development of the PC, associated with AC and STEAM, aimed at the early years of elementary school, but which also contemplate the "low floor", one of the assumptions of AC, for any student cycles